Probiotics for maintenance of remission in ulcerative colitis - Iheozor-Ejiofor, Zipporah (Cochrane Database Syst Rev, 2020)
BACKGROUND: Ulcerative colitis is an inflammatory condition affecting the colon, with an annual incidence of approximately 10 to 20 per 100,000 people. The majority of people with ulcerative colitis can be put into remission, leaving a group who do not respond to first‐ or second‐line therapies. There is a significant proportion of people who experience adverse effects with current therapies. Consequently, new alternatives for the treatment of ulcerative colitis are constantly being sought. Probiotics are live microbial feed supplements that may beneficially affect the host by improving intestinal microbial balance, enhancing gut barrier function and improving local immune response. OBJECTIVES: The primary objective was to determine the efficacy of probiotics compared to placebo, no treatment, or any other intervention for the maintenance of remission in people with ulcerative colitis. The secondary objective was to assess the occurrence of adverse events associated with the use of probiotics. SEARCH METHODS: We searched CENTRAL, MEDLINE, Embase, and two other databases on 31 October 2019. We contacted authors of relevant studies and manufacturers of probiotics regarding ongoing or unpublished trials that may be relevant to the review, and we searched ClinicalTrials.gov. We also searched references of trials for any additional trials. SELECTION CRITERIA: Randomised controlled trials (RCTs) that compared probiotics against placebo or any other intervention, in both adults and children, for the maintenance of remission in ulcerative colitis were eligible for inclusion. Maintenance therapy had to be for a minimum of three months when remission has been established by any clinical, endoscopic,histological or radiological relapse as defined by study authors. DATA COLLECTION AND ANALYSIS: Two review authors independently conducted data extraction and 'Risk of bias' assessment of included studies. We analysed data using Review Manager 5. We expressed dichotomous and continuous outcomes as risk ratios (RRs) and mean differences (MDs) with 95% confidence intervals (CIs). We assessed the certainty of the evidence using the GRADE methodology. MAIN RESULTS: In this review, we included 12 studies (1473 randomised participants) that met the inclusion criteria. Participants were mostly adults. The studies compared probiotics to placebo, probiotics to 5‐aminosalicylic acid (5‐ASA) and a combination of probiotics and 5‐ASA to 5‐ASA. The studies ranged in length from 12 to 52 weeks. The average age of participants was between 32 and 51, with a range between 18 and 88 years. Seven studies investigated a single bacterial strain, and five studies considered mixed preparations of multiple strains. The risk of bias was high in all except three studies due to selective reporting, incomplete outcome data and lack of blinding. This resulted in low‐ to very low‐certainty of evidence. It is uncertain if there is any difference in occurrence of clinical relapse when probiotics are compared with placebo (RR 0.87, 95% CI 0.63 to 1.18; 4 studies, 361 participants; very low‐certainty evidence (downgraded for risk of bias, imbalance in baseline characteristics and imprecision)). It is also uncertain whether probiotics lead to a difference in the number of people who maintain clinical remission compared with placebo (RR 1.16, 95% CI 0.98 to 1.37; 2 studies, 141 participants; very low‐certainty evidence (downgraded for risk of bias, imbalance in baseline characteristics and imprecision)). When probiotics are compared with 5‐ASA, there may be little or no difference in clinical relapse (RR 1.01, 95% CI 0.84 to 1.22; 2 studies, 452 participants; low‐certainty evidence) and maintenance of clinical remission (RR 1.06, 95% CI 0.90 to 1.25; 1 study, 125 participants; low‐certainty evidence). It is uncertain if there is any difference in clinical relapse when probiotics, combined with 5‐ASA are compared with 5‐ASA alone (RR 1.11, 95% CI 0.66 to 1.87; 2 studies, 242 participants; very low‐certainty evidence (downgraded due to risk of bias and imprecision)). There may be little or no difference in maintenance of remission when probiotics, combined with 5‐ASA, are compared with 5‐ASA alone (RR 1.05, 95% CI 0.89 to 1.24; 1 study, 122 participants; low‐certainty evidence). Where reported, most of the studies which compared probiotics with placebo recorded no serious adverse events or withdrawals due to adverse events. For the comparison of probiotics and 5‐ASA, one trial reported 11/110 withdrawals due to adverse events with probiotics and 11/112 with 5‐ASA (RR 1.02, 95% CI 0.46 to 2.25; 222 participants; very low‐certainty evidence). Discontinuation of therapy was due to gastrointestinal symptoms. One study (24 participants) comparing probiotics combined with 5‐ASA with 5‐ASA alone, reported no withdrawals due to adverse events; and two studies reported two withdrawals in the probiotic arm, due to avascular necrosis of bilateral femoral head and pulmonary thromboembolism (RR 5.29, 95% CI 0.26 to 107.63; 127 participants; very low‐certainty evidence). Health‐related quality of life and need for additional therapy were reported infrequently. AUTHORS' CONCLUSIONS: The effectiveness of probiotics for the maintenance of remission in ulcerative colitis remains unclear. This is due to low‐ to very low‐certainty evidence from poorly conducted studies, which contribute limited amounts of data from a small number of participants. Future trials comparing probiotics with 5‐ASA rather than placebo will better reflect conventional care given to people with ulcerative colitis. Appropriately powered studies with a minimum length of 12 months are needed.